2020
DOI: 10.26434/chemrxiv.13055873
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Specific and Rapid SARS-CoV-2 Identification Based on LC-MS/MS Analysis

Abstract: This study describes the development of a novel assay for SARS-CoV-2 identification using LC-MS/MS analysis. A multi-step procedure for the rational down-selection of a set of markers has leaded to the discovery of six SARS-CoV-2 specific and sensitive markers, enabling the reliable identification of the virus. A rapid and simple assay was developed, successfully applied to clinical nasopharyngeal samples. The assay may potentially serve as a complementary approach for SARS-CoV-2 identification.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Currently, nucleic acid-based assays (e.g., PCR) are being used as a gold standard for diagnostic testing of SARS-CoV-2 and other viruses in clinical platforms. However, many recent studies showed MS-based assay has the potential to supplement the diagnostic testing of COVID-19 [5,14,[28][29][30][31][32][33][34][35]. Therefore, the development of rapid, sensitive, and multiplexed LC-MS/MS methods could be an attractive alternative in the COVID-19 testing field.…”
Section: Ms-based Targeted Proteomic Methods Offers Highly Reproducible Multiplexed Diagnostic Tools For Covid-19mentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, nucleic acid-based assays (e.g., PCR) are being used as a gold standard for diagnostic testing of SARS-CoV-2 and other viruses in clinical platforms. However, many recent studies showed MS-based assay has the potential to supplement the diagnostic testing of COVID-19 [5,14,[28][29][30][31][32][33][34][35]. Therefore, the development of rapid, sensitive, and multiplexed LC-MS/MS methods could be an attractive alternative in the COVID-19 testing field.…”
Section: Ms-based Targeted Proteomic Methods Offers Highly Reproducible Multiplexed Diagnostic Tools For Covid-19mentioning
confidence: 99%
“…This finding is significant, as clinical samples are often dilute and have a low viral load. More recently, multiple MS-based targeted protocols have been developed and successfully applied to detect SARS-CoV-2 proteins including N, S, and M proteins from various clinical samples [28][29][30][31][32][33][34][35]. Despite these successful pilot studies, potential challenges and technical limitations of virus diagnostics using MS-based method from clinical samples F I G U R E 5 Potential bottom-up proteomics platforms for elucidation of the molecular mechanisms of SARS-CoV-2 infection.…”
Section: Ms-based Targeted Proteomic Methods Offers Highly Reproducible Multiplexed Diagnostic Tools For Covid-19mentioning
confidence: 99%
See 1 more Smart Citation